2016
DOI: 10.1016/j.pupt.2016.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Targeted drug delivery to emphysematous lungs: Inhibition of MMPs by doxycycline loaded nanoparticles

Abstract: Graphical Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 56 publications
0
17
0
Order By: Relevance
“…In short, results showed that the delivery of the drug to neutrophils in murine models of obstructive lung diseases was able to control neutrophil-inflammation and subsequent lung disease thereby highlighting the potential clinical utility of polymeric NPs for asthma and COPD ( Vij et al, 2016 ). In a study targeted to repair the ECM, researchers utilized BSA NPs encapsulated with DOX to regenerate the degraded elastic tissue for emphysema ( Parasaram et al, 2016 ). The NPs were optimized for their size (∼175 nm), surface properties (-60 mV), yield (∼34%), drug encapsulation efficiency (∼17%), and release properties (∼9.7% over 24 h and ∼14% over 48 h) ( Parasaram et al, 2016 ).…”
Section: Nanomaterials To Modulate the Lung Tissue Microenvironmentmentioning
confidence: 99%
See 3 more Smart Citations
“…In short, results showed that the delivery of the drug to neutrophils in murine models of obstructive lung diseases was able to control neutrophil-inflammation and subsequent lung disease thereby highlighting the potential clinical utility of polymeric NPs for asthma and COPD ( Vij et al, 2016 ). In a study targeted to repair the ECM, researchers utilized BSA NPs encapsulated with DOX to regenerate the degraded elastic tissue for emphysema ( Parasaram et al, 2016 ). The NPs were optimized for their size (∼175 nm), surface properties (-60 mV), yield (∼34%), drug encapsulation efficiency (∼17%), and release properties (∼9.7% over 24 h and ∼14% over 48 h) ( Parasaram et al, 2016 ).…”
Section: Nanomaterials To Modulate the Lung Tissue Microenvironmentmentioning
confidence: 99%
“…In a study targeted to repair the ECM, researchers utilized BSA NPs encapsulated with DOX to regenerate the degraded elastic tissue for emphysema ( Parasaram et al, 2016 ). The NPs were optimized for their size (∼175 nm), surface properties (-60 mV), yield (∼34%), drug encapsulation efficiency (∼17%), and release properties (∼9.7% over 24 h and ∼14% over 48 h) ( Parasaram et al, 2016 ). Release kinetics of DOX from the BSA NPs led to significant inhibition of MMPs in the lung for up to 4 weeks in vivo utilizing Sprague Dawley rat models ( Parasaram et al, 2016 ).…”
Section: Nanomaterials To Modulate the Lung Tissue Microenvironmentmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, DOXY-PNPs were prepared to enhance its antibacterial activity against some types of bacteria [ 20 ] or to reduce its toxicity [ 21 ]. Meanwhile, as an antitumor agent, some types of DOXY nanoparticles were prepared to enhance its penetration into cancer cells [ 22 ], augment its anticancer activity [ 23 ] or improve drug delivery and efficacy [ 24 , 25 ] however, DOXY-PNPs were not designed before.…”
Section: Introductionmentioning
confidence: 99%